[OP.5C.01] STATUS OF CARDIOVASCULAR HEALTH IN CHINESE CHILDREN AND ADOLESCENTS. (September 2017) - Mi, J.; Yan, Y.; Dong, H.
Abstract : Objective: In 2010, the American Heart Association (AHA) defined a set of four health behaviors and four health factors to evaluate cardiovascular health (CVH) status for children and adolescents. We aimed to examine the age-, sex-, and region- specific prevalence of ideal CVH and each CVH component among Chinese children and adolescents based on a nationally representative survey. Design and method: Data were obtained from the China Children and Adolescents Cardiovascular Health study conducted in 2013–2014, which comprised of 10 818 children and adolescents aged 6–18 years old from eight cities. Seven CV health metrics, including smoking, body mass index, dietary intake, physical activity, blood pressure, blood glucose, and total cholesterol, are categorized as poor, intermediate, and ideal according to AHA criteria. Results: Ideal smoking status was most prevalent (males, 93.6%; females, 96.7%), whereas ideal physical activity levels (males, 9.1%; females, 5.6%) and ideal Health Diet Score (males, 18.8%; females, 19.3%) were least prevalent. Females had a higher prevalence of ideal body mass index (79.8% vs 65.6%) and ideal blood pressure (73.1% vs 66.2%). The overall prevalence of ideal CVH among Chinese children and adolescents was very low (males, 0.4%; females, 0.6%). The prevalence of ideal CVH decreased with age, and children aged 6–11 years versus adolescents aged 12–18 years had a higher prevalence of ideal CVH. Prevalence estimates according to age and sex were consistent across region. Children with adverse health behaviors scores had a lower prevalence of ideal blood pressure, ideal blood glucose, and ideal total cholesterol. Conclusions: We found a very low prevalence of ideal CVH in Chinese children and adolescents, particularly physical activity and dietary intake. The current worsening of CVH status among Chinese children and adolescents would lead to epidemic of obesity, hypertension, hypercholesterolemia, and diabetes when they step into adulthood.